A phosphorus–carbon framework over activated carbon supported palladium nanoparticles for the chemoselective hydrogenation of para-chloronitrobenzene. Issue 7 (21st March 2017) - Lu, Chunshan; Wang, Mengjun; Feng, Zhenlong; Qi, Yani; Feng, Feng; Ma, Lei; Zhang, Qunfeng; Li, Xiaonian
Abstract : A novel Pd–P–C framework structure was fabricated. Pd with electron-rich properties exhibits superior selectivity up to 99.9% for the hydrogenation of p -CNB to p -CAN. Abstract : A novel Pd–P–C framework structure was fabricated by supporting Pd on a P-doped carbon layer coated with activated carbon. A P-doped carbon layer was generated via calcination of sodium hypophosphite and ethanediol under inert gas atmosphere. The catalysts were characterized by Brunauer–Emmett–Teller (BET) analysis, X-ray diffraction (XRD), transmission electron microscopy (TEM), Raman spectroscopy and X-ray photoelectron spectroscopy (XPS) and were evaluated in the selective hydrogenation of p -CNB to p -CAN. The results indicate that the carbon layer generated via calcination of ethanediol presents a higher disordered structure and then the P-doped carbon layer becomes more ordered due to the formation of a P–C framework. Some electrons were transferred from C atoms adjacent to the P atoms to P atoms, which favors the formation of stable Pd–P species such as the Pd15 P2 phase. Pd in the Pd–P–C framework structure possesses electron-rich properties resulting from electron transfer from C atoms to Pd atoms via P atoms, which induces the formation of electron-rich hydrogen (H − ) when hydrogen was absorbed on the Pd particles. The produced electron-rich H − might prefer the nucleophilic attack on the nitro group rather than the electrophilic attack on the C–Cl bond. We suggest that it is responsible for the superior selectivity of up to 99.9% to p -CAN for the hydrogenation of p -CNB. The catalytic performance of the Pd particles supported on the P-doped carbon layer remains unchanged after five cycles indicating excellent stability.